INFLUENCE OF NEUTRAL RED ON THE ECONOMIC, REPRODUCTIVE AND BIOCHEMICAL PARAMETERS OF SILKWORM BOMBYX MORI. L (International Journal of Food and Nutritional Sciences, 2022)
Nutritional requirement in food consumption have direct impact on the overall growth ofsilkworm and also increase the cocoon weight, cocoon length, shell weight, pupal weight,pupal length, silk length, silk weight, denier, moth efflorescence, fecundity, fertilized egg,unfertilized egg, hatching percentage and brushing percentage, carbohydrate, amino acid andprotein in haemolymph and silk Gland of B.mori.